PIK3CA mutations in breast cancer with low HER2 / neu expression - I. A. Pavlenko; P. E. Povilaitite; V. Yu. Kaciyaev; N. S. Makarevich; A. V. Petrov (Успехи молекулярной онкологии, 2022)
Introduction. Disturbances in the PI3K-dependent (PI3K – phosphoinositide 3‑kinase) cascade are characteristic of all types of breast cancer. In particular, 30–40 % of patients with advanced / metastatic hormone-positive HER2‑negative (HER2 – human epidermal growth factor receptor 2) breast cancer carry PIK3CA mutations in tumor cells. The detection of these mutations in patients with hormone-positive HER2‑negative breast cancer is of great clinical importance, since they are a predictor of tumor sensitivity to the PI3K inhibitor alpelisib. According to the HER2 / neu protein expression status, all patients with hormone-positive HER2‑negative breast cancer can be divided into two groups – with low expression of HER2 / neu (scores 0, 1+ or 2+ per immunohistochemical analysis and negative result of in situ hybridization) and with a complete lack of expression of this protein.Aim. To establish whether there are differences in the nature and prevalence of PIK3CA mutations in patients in these two groups.Materials and methods. The study was carried out on 32 breast cancer samples with a luminal HER2‑negative immunophenotype, which were divided into two groups – with low HER2 / neu expression (n = 15) and with a complete absence of HER2 / neu expression (n = 17). PIK3CA mutations were determined using the commercially available cobas PIK3CA MutationTest kit (Roche, Switzerland) by real-time polymerase chain reaction on paraffin block material (tissue biopsy).Results. Mutations of the PIK3CA gene were detected in 37.5 % of cases, of which p.E542K mutation was detected in 2 cases; p.E545X – in 3, p.H1047X – in 6 and p.N345K – in 1. Analysis of the mutational status of both groups revealed statistically significant differences in the quantitative distribution of PIK3CA mutations. The frequency of PIK3CA mutations was significantly higher in tumors with low expression of HER2 / neu (p = 0.0268). Thus, characteristic genetic changes have been identified for a group of patients with HER2‑low breast cancer. These changes are potential targets for therapy, which is important for clinical practice, as it opens up new therapeutic possibilities for breast cancer patients with low HER2 / neu expression.